2017
DOI: 10.3390/atmos8100197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Fluxes in the WRF Model: Case Study for Farmland in Rolling Terrain

Abstract: Abstract:The partitioning of available energy into surface sensible and latent heat fluxes impacts the accuracy of simulated near surface temperature and humidity in numerical weather prediction models. This case study evaluates the performance of the Weather Research and Forecasting (WRF) model on the simulation of surface heat fluxes using field observations collected from a surface flux tower in Oregon, USA. Further, WRF-modeled heat flux sensitivities to North American Mesoscale (NAM) and North American Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Mesoscale numerical weather prediction models such as the Weather Research and Forecasting (WRF) model provide detailed data sets at higher resolution compared with reanalysis data. We make use of the sign of the WRF simulated SHF for statistical analyses and assume the sign of the SHF to be better simulated than sign and magnitude . However, temporal difference of times associated with positive and negative SHF between model and measurement will lead to occasional mismatch of transition times as well as random errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoscale numerical weather prediction models such as the Weather Research and Forecasting (WRF) model provide detailed data sets at higher resolution compared with reanalysis data. We make use of the sign of the WRF simulated SHF for statistical analyses and assume the sign of the SHF to be better simulated than sign and magnitude . However, temporal difference of times associated with positive and negative SHF between model and measurement will lead to occasional mismatch of transition times as well as random errors.…”
Section: Introductionmentioning
confidence: 99%
“…We make use of the sign of the WRF simulated SHF for statistical analyses and assume the sign of the SHF to be better simulated than sign and magnitude. 11,12 However, temporal difference of times associated with positive and negative SHF between model and measurement will lead to occasional mismatch of transition times 13 as well as random errors. We believe that these errors are statistically insignificant for the overall evaluation but are aware of the resulting inaccuracy.…”
mentioning
confidence: 99%
“…Moreover, this strong overestimation of the SH flux was also observed in the simulations carried out in the area of Cabauw from the WRF model in Steeneveld et al (), although the temperature profiles were adequately reproduced. Sun et al () found an overestimation of the SH flux of similar magnitude using the YSU ABL scheme in their simulations from the WRF model, but in this case producing a positive bias in the 2‐m air temperature. On the other hand, it must also be taken into account that measurements tend to underestimate the turbulent fluxes as reported for instance in Foken ().…”
Section: Assessment Of the Model Performancementioning
confidence: 99%
“…The influencing factors involved in the process of surface energy exchange are complex, and surface temperature, wind speed, terrain, and other factors should be taken into account in follow-up research [54][55][56]. In subsequent research on surface energy exchange, attention should be paid to the comprehensive processes of various factors, including LST, as well as to advanced mathematical models [57,58]. Furthermore, the factors affecting crop yield in the study area are relatively complex.…”
Section: Research Limitations and Future Prospects Of The Paddy Expanmentioning
confidence: 99%